PENERAPAN LEMARI ASAP TERKONTROL UNTUK PRODUKSI TELUR ASIN ASAP DI INDUSTRI RUMAH TANGGA ELDONA, BANJARBARU - Muhammad Saukani; Irfan Irfan; Achmad Jaelani (LP2M Universitas Hasanuddin, 2019)
Application of Controlled Smoke Cabinet for the Production of Smoked Salt Egg in the Eldona Home Industry, BanjarbaruAbstract. The Telur Asin Eldona Home Industry have problems in the process of producing salted smoke eggs. Production rate only 800-1000 salted smoke eggs per week. The fumigation time takes up to three days. The high defect products reach 20% due to overheating during the fumigation process. The community partnership program aims to increase the volume of production of salted smoke eggs and reduce product failures in the fumigation process. To achieve this goal, Designing a larger smoke cabinet applying a pyrolysis system and temperature control to avoid overheating. The rack of salted egg placement is practically modified to be flipped and shifted. The results of the initial implementation at the